Effect of soil and foliar application of micronutrients and fungicides on late blight (Phytophthora infestans) and tuber yield of potato (Solanum tuberosum) - Trehan, S P; Sharma, K K; Grewal, G S (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during the winter season of 1991-92 and 1992-93 to study the effect of micro nutrients (Zn,Cu, Mo and Mn) and fungicides (metalaxyl + mancozeb (Ridomil MZ 72 wp) and mancozeb (Dithane M-45)] on the development oflate blight [Phytophthora infestans (Mont.) de Bary) and tuber yield of 'Kufri Chandramukhi' potato (Solanum tuberosum L.).The effectiveness of micro nutrients was more at low disease incidence and was at par with metalaxyl + mancozeb. Foliarsprays of micronutrients (Zn, Cu, Zn + Cu + Mo) proved effective in reducing late blight (65.4- 92.6%) and increasing tuberyield (36.3-45.9%). However, in blight-epidemic year the micronutrients (Zn + Cu + Mo + Mn) and mancozeb gave the significantcontrol (42.5 and 31.2% respectively) of late blight, but were less effective than systemic fungicide metalaxyl + mancozeb(95.7%). Soil application of micronutrients did not show effect on the development of late blight and tuber yield.Late-blight infection in harvested tubers was positively correlated with its intensity on foliage.